DETERMINATION OF PARAMETERS OF LENGTHWISE ROLLING PROCESS FOR OBTAINING STRIPS OF VARIABLE THICKNESS WITH INCREASING REDUCTION - L. A. Isaevich; M. I. Sidorenko; D. M. Ivanitski; M. M. Malekian (Наука и техника)
The paper considers problems pertaining to determination of calculated values of a critical angle in the case of rolling strips of variable thickness with increasing reduction. Equations for calculation of an average normal contact pressure and rolling moment are obtained in the paper.